2019
DOI: 10.1007/s10648-019-09465-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Architecture and Instructional Design: 20 Years Later

Abstract: Cognitive load theory was introduced in the 1980s as an instructional design theory based on several uncontroversial aspects of human cognitive architecture. Our knowledge of many of the characteristics of working memory, long-term memory and the relations between them had been well-established for many decades prior to the introduction of the theory. Curiously, this knowledge had had a limited impact on the field of instructional design with most instructional design recommendations proceeding as though worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,401
3
79

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,308 publications
(1,760 citation statements)
references
References 115 publications
31
1,401
3
79
Order By: Relevance
“…To overcome these challenges, medical educators have employed new instructional strategies, including problem‐based learning, novel online course materials and other integrative course designs . These instructional strategies leverage theories from educational psychology, including cognitive load theory (CLT), which provides a framework to understand the relationship between human cognitive architecture, mental effort and learning performance . It has been utilised to generate instructional principles for designing anatomical multimedia and generalisable design guidelines for medical education .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, medical educators have employed new instructional strategies, including problem‐based learning, novel online course materials and other integrative course designs . These instructional strategies leverage theories from educational psychology, including cognitive load theory (CLT), which provides a framework to understand the relationship between human cognitive architecture, mental effort and learning performance . It has been utilised to generate instructional principles for designing anatomical multimedia and generalisable design guidelines for medical education .…”
Section: Introductionmentioning
confidence: 99%
“…To summarise, a broad review of the literature across several domains has revealed that scholars agree that a lack of awareness of one's emotions may lead to biased decision making . However, little is currently known about the impact of raters’ emotions on the decision‐making process of entrustment of residents in clinical settings.…”
Section: Emotions and Decision‐making Tasksmentioning
confidence: 99%
“…Richard Mayer’s cognitive theory of multimedia learning particularly provides a conceptual framework to describe how learners process multimedia 1,2. According to Allan Paivio and modified by Mayer, individuals process materials into either a visual or auditory channel within their working memory, each having a finite capacity.…”
Section: Introductionmentioning
confidence: 99%